Physical activity level and sedentary behaviour among healthy school children in spain measured by triaxial accelerometry - Benítez-Porres, Javier; López-Fernández, Iván; Alvero-Cruz, José Ramón; Álvarez-Carnero, Elvis (ECSS, 2017)
Introduction Physical inactivity and sedentary behaviour has been identified as risk factors of childhood obesity and cardiovascular diseases. Triaxial accelerometers provide an objective indicator of free-living physical activity (PA). The purpose of this study was to describe levels and patterns of PA and sedentary time (ST) in Spanish children. Methods Data from 316 (n=166 boys, n=150 girls) healthy students (Age: 11.1±1.3 years, BMI: 19.8±3.6 kg/m2) enrolled in fourth, fifth or sixth grade, from the south, central and north of Spain, were used. The Actigraph GT3X monitor device was used to assess PA. Accelerometers were set to register 1-second epoch cycles, and were programmed to assess 7 days. We selected the cut points from Evenson et al. to determine the time spent on different intensity levels of PA and ST. Results Accelerometer data revealed that children spent an average of 54.4±17.8 min/day in moderate-to-vigorous PA (MVPA) and were sedentary for an average of 10 hours per day (619.2±67.3 min/day). Accumulation of 60 min/day of MVPA was achieved by 37.7% of the students. There was a significant difference in MVPA and ST between boys and girls (MVPA 58.3±16.9 vs 49.9±17.7 min/day, p<0.001; ST 609.8±66.1 vs 629.6±67.4 min/day, p<0.01; respectively). Boys performed 9865 steps/day, while girls performed 9119 steps/day (p<0.05). Discussion Our results suggest that a high percentage of Spanish schoolchildren do not meet PA and daily steps recommendations, where boys are more active than girls. Children spent most of their time in sedentary activities and light PA. Spanish government should consider launching campaigns against sedentary behaviour in schools in order to increase MVPA daily level. References Benítez-Porres J, Alvero-Cruz, JR, Sardinha, LB, Lopez-Fernandez I, Carnero EA (2016). Nutr Hosp, 33(5), 1036-1044. Cesa CC, Sbruzzi G, Ribeiro RA, Barbiero SM, de Oliveira Petkowicz R, Eibel B, Pellanda LC (2014). Prev Med, 69, 54-62. Cordova A, Villa G, Sureda A, Rodriguez-Marroyo JA, Sanchez-Collado MP (2012). Rev Esp Cardiol, 65(7), 620-626. Evenson KR, Catellier DJ, Gill K, Ondrak KS, McMurray RG (2008). J Sports Sci, 26(14), 1557-1565. WHO (2010). 58, Switzerland. Contact benitez@uma.es
Keywords: Educación física